Policy response to commodity price fluctuations: The case of Nigeria - Magnus O. Abeng; Margaret J. Hilili (West African Journal of Monetary and Economic Integration, 2017)
Commodity price shocks have, over the years, posed major challenges for the conduct of monetary policy and economic management in Nigeria. Several studies dedicated to investigating these phenomena had focused only on oil price (Nigeria's major commodity) with little or no attention to food price shock. In this study, however, the effect of food price shocks on some selected macroeconomic indicators is examined, in addition to oil price shock using the structural autoregressive (SVAR) model. Evidence from the results show that exchange rate and interest rate responses to net oil and food price shocks is negative, while inflation response is mixed. The contribution to the variation in the macroeconomic variables by oil price shocks is found to be more profound compared with food price shock. Further evidence identified the exchange rate channel as the dominant channel for the transmission of both oil and food price shocks to the domestic economy. This is followed by interest rate and stock returns channels, in the cases of oil and food price shocks, respectively. This intuitively suggests the prioritisation of these channels in the design and conduct of monetary policy, if the monetary authority has to deliver on the 'price stability' and 'stable exchange rate' mandate for inclusive and sustainable growth.
Keywords: F42; E52; 330; Monetary Policy; Impulse Response; Commodity prices; SVAR